ПРЕПОЗНАВАЊЕ ЛИЦА У ПРЕДИСТРАЖНОМ ПОСТУПКУ И ИСТРАЗИ: АКТУЕЛНЕ КОНТРОВЕРЗЕ И ПРАКСА ВРХОВНОГ КАСАЦИОНОГ СУДА - Tasić, Marija; Žarković, Milan; Bul, Rej (NBP. Nauka, bezbednost, policija, 2023)
The present article analyses the case-law of the Supreme Court of Cassation of the Republic of Serbia regarding identification of persons conducted in pre-investigation proceedings and investigation by the police. The basic assumption is that the quality and precision of the criminal procedure rules and judgments of the Supreme Court of Cassation additionally determine the police actions in the conditions of expected harmonization of these rules with the most important scientific findings on factors (‘system variables’) that affect the accuracy of identification. In order to determine how the case-law in Serbia treats certain assertions made in the requests for protection of legality regarding violations of criminal procedure regarding identification of persons, the present article analyzed 33 judgments issued by the Supreme Court of Cassation regarding these requests in the period from 2013 to 2021. Based on the results of the analysis, recommendations regarding improvement of the current criminal procedure rules referred to the identification of persons in Serbia were provided, and that by respecting research-informed standards for the collection, preservation, and presentation of identification evidence.
Keywords: препознавање лица, контраверзе, кривично процесна правила, судска пракса, полиција